1999
DOI: 10.1088/1464-4258/1/6/306
|View full text |Cite
|
Sign up to set email alerts
|

On the properties of two pulses propagating simultaneously in different dispersion regimes in a nonlinear planar waveguide

Abstract: Properties of two pulses propagating simultaneously in different dispersion regimes, anomalous and normal, in a Kerr-type planar waveguide are studied in the framework of the nonlinear Schrödinger equation. It is found that the presence of the pulse propagating in a normal dispersion regime can cause termination of catastrophic self-focusing of the pulse with anomalous dispersion. It is also shown that the coupling between pulses can give rise to spatiotemporal splitting of the pulse propagating in anomalous d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
(113 reference statements)
2
15
0
Order By: Relevance
“…For OMs, some previous authors reported that nonlinearity necessary for catastrophic self-focusing in a configuration of two beams is approximately three times smaller than in the case when they propagate as single beam [20][21][22][23]. Therefore, under the action of XPM, Figure 2(b) shows that peak intensity of both waves will monotonically increase with increasing propagation until collapse occurs, agreeing with the results obtained in [36][37][38][39]. However, for MMs, the situation becomes qualitatively different, as can be seen from Figure 2(a).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…For OMs, some previous authors reported that nonlinearity necessary for catastrophic self-focusing in a configuration of two beams is approximately three times smaller than in the case when they propagate as single beam [20][21][22][23]. Therefore, under the action of XPM, Figure 2(b) shows that peak intensity of both waves will monotonically increase with increasing propagation until collapse occurs, agreeing with the results obtained in [36][37][38][39]. However, for MMs, the situation becomes qualitatively different, as can be seen from Figure 2(a).…”
Section: Resultssupporting
confidence: 87%
“…Case (i) is similar to the conventional materials, while case (ii) is simple since optical wave always spread even for very large strengths of self-focusing nonlinearity [36][37][38][39]. Therefore, in the following, we will only in detail discuss the last case (iii) unseen in OMs, paying attention to collapse of probe wave arrested by XPM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations